Peran Pendidik Mental Spritualitas Islam Dalam Membentuk Karakter Penghuni Rutan di Wonosobo - Firman Nur Karim; Ngarifin Shidiq; Muhammad Saefullah (Jurnal Kajian dan Penelitian Umum, 2024)
This research is an effort to determine the role of Islamic spiritual mental education in forming character for detention center inmates in Wonosobo. The questions to be answered through this research are: a. How is the implementation of Islamic mental spirituality education in the Wonosobo Detention Center? b. What are the methods and approaches used in Islamic spiritual mental education at the Wonosobo Detention Center? and c. What are the supporting and inhibiting factors in implementing Islamic mental spirituality education in the Wonosobo Detention Center? The research method used is field research. This research was carried out using observation, interview and documentation data collection techniques. The field data was analyzed using descriptive analysis. The results of the research show that the implementation of Islamic mental spirituality education in the Wonosobo Detention Center includes: consisting of Personality Development and Independence Development. The methods and approaches used in Islamic spiritual mental education at the Wonosobo Detention Center include: Lectures, Group discussions, Questions and answers, Individual mentoring, Worship practices, Self-reflection, Role-playing, Case studies, Use of audio-visual media and Spiritual therapy. Meanwhile, the general approaches used include, humanist approach, gradual approach, holistic approach, contextual approach, participatory approach. Meanwhile, supporting and inhibiting factors in the implementation of Islamic mental spirituality education in Wonosobo Detention Center include: a. Limited Resources, b. Resistance of Some Prisoners, c. Lack of Interest or Distrust.